An indicator of inefficient visualizations: the challenge of transparency during the COVID-19 pandemic in Brazil - Oliveira, Rodrigo; Cappelli, Claudia; Oliveira, Jonice (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
The COVID-19 epidemic requires clear and reliable information to guide the population. Visualization is a powerful tool to contribute to the understanding of this data. However, just divulging this resource is not enough to guarantee this understanding. It is important to support users in analyzing this data, making this process easier and more transparent, especially for users with little (or no) literacy. In this work, we define an inefficient graphics indicator, that is, with the potential to be misinterpreted or difficult to understand, according to the basic guidelines of the data visualization area. These guidelines were selected through a literature review, forming a repository of practices that guide good visualization design and provide the indicator assessment items. This proposal can be applied inis necessary because we do not perceive the existence of standards, norms or quality indicators for data visualization that assist in the creation of this artifact efficiently or evaluate the existing ones for improvement, both manually and automatically. This approach can be applied in the most diverse scenarios, being initially in Brazil during the dissemination of COVID-19, analyzing the official visualizations and highlighting the failures of several epidemiological perspectives on the pandemic. Through a study with users where volunteers analyzed the official data and our recommendations, we demonstrated that the indicator is effective in detecting and helping to understand the visualization. We highlight the alert for the need for greater care in the creation of graphics by the government so as not to compromise the understanding of the citizens who use them.